Frontotemporal Dementia and Late-Onset Bipolar Disorder: The Many Directions of a Busy Road - Maia da Silva, Mari N.; Porto, Fábio Henrique de Gobbi; Lopes, Pedro Maranhão Gomes; Sodré de Castro Prado, Catarina; Frota, Norberto Anízio Ferreira; Alves, Candida Helena Lopes; Alves, Gilberto Sousa (Frontiers in Psychiatry, 2021)
It is a common pathway for patients with the behavioral variant of frontotemporal dementia (bvFTD) to be first misdiagnosed with a primary psychiatric disorder, a considerable proportion of them being diagnosed with bipolar disorder (BD). Conversely, not rarely patients presenting in late life with a first episode of mania or atypically severe depression are initially considered to have dementia before the diagnosis of late-onset BD is reached. Beyond some shared features that make these conditions particularly prone to confusion, especially in the elderly, the relationship between bvFTD and BD is far from simple. Patients with BD often have cognitive complaints as part of their psychiatric disorder but are at an increased risk of developing dementia, including FTD. Likewise, apathy and disinhibition, common features of depression and mania, respectively, are among the core features of the bvFTD syndrome, not to mention that depression may coexist with dementia. In this article, we take advantage of the current knowledge on the neurobiology of these two nosologic entities to review their historical and conceptual interplay, highlighting the clinical and neuroimaging features that may be unique to each of them.